A collection of songs from Sammlung Horak in Volksmusikarchiv des Bezirks Oberbayernw in light of the latest research on music in Wilamowice - Król, Tymoteusz (Literatura Ludowa. Journal of Folklore and Popular Culture, 2020)
Wilamowice was investigated by both Polish and German academics. Not only the history of the town, but as well the language, folk dress and traditions were investigated. Especially German scholars, who represented the movement of language island investigations – Sprachinselforschung, came to Wilamowice in 30s and 40s to explore the local culture. They have made a careful fieldwork, but unfortunately the nationalistic spirit of the times has strong influenced their later texts and interpretations. The Vilamovian music has been a very rare topic in academic investigations. The only one investigator, who made musicological fieldwork in Wilamowice was a German musicologist, Karl Horak, who has collected some notes and texts of songs and published some texts about the music in “bielsko-biała language island”, to which he included Wilamowice too. There was a book „Bez muzyki, bez śpiewu, nie ma świata. Muzyka w Wilamowicach” published in 2019, edited by dr Maria Małanicz-Przybylska, where I have published an appendix which all 47 collected by my Wymysorys-language songs. As the book had been already published, I found in Volksmusikarchiv Oberbayern another 20 texts of songsi, which were collected in Wilamowice by Karl Horak and Alfred Karasek in 1937. In this text, I compare this collection which the songs collected by me and published in the “Appendix”, and I publish their text, transliterated into the modern ortography of the Wymysorys language. I try to take note on possible influence of the nationalistic-German perspective of Horak to his interpretations.